Pre-conceptual design of a self-shutdown communicating vessels system for a small molten salt reactor. (November 2021) - Fradera, J.; Alberto, P.; Moya, G.; Bernad, A.; Catalán, D.; Fernández, A.; Garrido, C.
Highlights: A pre-conceptual design of a molten salt small modular reactor. Active components such as pumps are required for the reactor criticality to be maintained. Loss of active pumping enables the reactor to quickly enter into a shutdown state. A communicating vessels system is used to shut down the reactor passively. A multidisciplinary analysis is carried out to assess the feasibility of the concept. Preconceptual design shows no critical stoppers. Abstract: The present work exposes a communicating vessels closed system pre-conceptual design for a small Molten Salt Reactor (MSR). The fuel volume is kept in a critical configuration by using forced convection of an immiscible non-reactive neutron absorber with a higher density than that of the fuel. The absorber is pushed to make the fuel flow into the core. The fuel interfaces with the absorber that fills part of the communicating vessels system on one side, and with a cover gas at the top that closes the system and balances pressure on the other side. The reactor shuts down by the force of gravity when the forced convection stops and the fuel, together with the absorber and a cover gas, balance out to the equilibrium level on both sides of the system. Therefore, when the reactor shuts down, the absorber falls and fills the core effectively rendering the reactor sub-critical while the fuel is pushed upward to a non-critical safe configuration. The Self-Shutdown MSR (SS-MSR) has some key intrinsic safety aspects in addition to those of the MSRs. In its natural state, the SS-MSR is shut down as the absorber fills the core. Continuous pumping of the absorber is needed for the fuel to fill the core and the reactor to become critical. The criticality depends on the level of the fuel in the core. In the case of an emergency, the pumps that keep the fuel inside the core stop and the reactor shuts down passively as it regains natural state by the force of gravity. The SS-MSR concept is analysed by means of a representative simplified reactor that is analysed from the neutronic, thermal-hydraulic and mechanical points of view. The final aim of the study is to evaluate the communicating vessels system feasibility and to detect possible safety issues of the proposed concept as well as to make a decided step towards a safe design of a small reactor.